EFISIENSI DAN DAMPAK TRANSPORTASI ONLINE DALAM MENINGKATKAN KESEJAHTERAAN DRIVER GOJEK DI KOTA JAMBI - Ayuningsih, Fitri; Sembiring, Benar (Universitas Batanghari Jambi, 2021)
Abstract This study aims to (1) Analyze the efficiency of online transportation, the impact of online transportation and the welfare of Go-jek drivers in Jambi City, (2) To analyze the efficiency and impact of online transportation on improving the welfare of Gojek drivers in Jambi City. This research uses qualitative research with the type of phenomenon research. Data collection techniques were carried out by observation, interviews, and documentation study. Data analysis in this study consisted of taking notes in order to produce field notes and coding, classifying data, and drawing data conclusions or verification. From this research, it can be concluded that the efficiency of online transportation for motorbikes makes it easier for consumers to get the transportation they want only, with their smartphones and internet quota without having to come to the base. Where the rates offered by the Gojek application are quite cheap both in the order rates or services offered. In addition, even though the driver's monthly wage is not stated in the work contract, the income earned by the driver can meet the needs of his family. Keywords: Efficiency, Impact, Online Transportation, Welfare